(untitled) (Bangladesh Journal of Agricultural Research, 2010)
Genetic divergence among 19 eggplant genotypes was estimated using Mahalanobis’s D2 statistic. Altogether five clusters were formed. Cluster I contained the highest number of genotypes (7) and cluster IV and V contained the lowest (2). The pattern of distribution of genotypes from different geographical locations into five clusters was random, demonstrating that geographical isolation may not be the only factor causing genetic diversity. The highest intra-cluster distance was observed for cluster V (1.067) and the lowest for cluster III (0.916). The highest inter-cluster distance was observed between cluster IV and V (10.748). Cluster V recorded the highest mean for plant height at last harvest (cm), leaf blade length (cm), leaf blade diameter (cm), leaf pedicel length (cm), fruit pedicel length (cm), prickle on calyx. Whereas, number of branches per plant, fruit diametre (cm), individual fruit weight (g), fruit yield (t/ha) and prickle on fruit pedicel were in cluster II with the highest means. Therefore, more emphasis should be given on cluster V for selecting genotypes as parents for crossing with the genotypes of cluster II which may produce new recombinants with desired traits. Key Words: Genetic diversit; eggplant (Solanum melongena L.); cluster analysis. DOI: 10.3329/bjar.v34i4.5845 Bangladesh J. Agril. Res. 34(4) : 705-712, December 2009